Clinical observations of the effect of orthokeratology in children with myopic anisometropia. Issue 3 (June 2020) - Lu, Weiwei; Jin, Wanqing
Abstract: Purpose: To evaluate the clinical effect of orthokeratology in controlling myopia and treating anisometropia among children with myopic anisometropia. Methods: A total of 108 myopic anisometropic children aged 8–16 years old who wore orthokeratology lenses in both eyes were enrolled in this study and followed up for over 1 year. The more severely myopic eye of each patient was assigned to the more myopic group (108 eyes), with a mean spherical equivalent refraction of −4.25 (−5.00, −3.38) D; the opposite eye of each patient was assigned to the less myopic group (108 eyes), with a refraction of −2.75 (−3.63, −1.88) D. This study observed and analyzed changes in ocular parameters after orthokeratology (Wilcoxon signed-rank test). Results: In children who wore orthokeratology lenses for approximately 1 year, the level of anisometropia significantly dropped from 1.38 (1.13, 1.75) D to 1.25 (1.13, 1.75) D ( P = .005). The difference between the axial lengths of the two eyes significantly dropped from 0.54 (0.37, 0.74) mm to 0.46 (0.28, 0.67) mm ( P < .0001). Conclusions: Orthokeratology seemed to be more effective at delaying the progression of myopia in the more myopic eyes than in the less myopic eyes of myopic anisometropic children. Orthokeratology lenses are suitable for anisometropic children, although the effectiveness of orthokeratology against anisometropia requires additional follow-up time for further observation and study.